10. MENELUSURI TINDAK KEKERASAN DI TANAH AIR - Turtiantoro, Turtiantoro (Faculty of Social and Political Sciences Diponegoro University, 2008)
History of Indonesian nation up to now notes various grieves, misery and social difference, which caused by unjust behavior and discrimination on the basis of ethnic , race, skin colour, culture, language, religion, faction, gender, and other social status. Unjust behavior and discrimination is human right collision.